Comparative analysis of spring mechanisms of vibroprotective chairs of road construction machines - Korytov M.S.; Sherbakov V.S.; Pochekueva I.E. (Научно-технический вестник Брянского государственного университета)
Reduction of vibrations of the human operator of road and construction machinery, emerging and transmissible human operator through his workplace while driving cars, is an important task, since the vibration of the human operator adversely affect the processes of its life, performance and fatigue, precision machine executable operations etc. The advantages for use of vibration isolation systems have mechanical devices without the use of hydraulic and electric components as the more reliable and durable. Among them can be highlighted Vibration system using hopping mechanisms. Hopping mechanism provides a negative stiffness when force produced by a similar mechanism, co-directed the deviation from the equilibrium position, and increases with the deviation. The combination of such a mechanism with conventional spring provides a quasi-zero stiffness. According to the developed kinematic schemes of three jump mechanisms considered as an example: Mezis truss, rhombus mechanism, and three-point mechanism, analytical equations are constructed by direct inference that relate the value of the deflecting force of the mechanism from the movement of the working point associated with the payload in the form of a chair with a person the operator. The obtained analytical dependencies allowed a comparative analysis of the static characteristics of the three mechanisms with a jump. The overall dimensions of the mechanisms and the stiffness of the springs were taken equal. The graphs of vertically directed forces created by the considered mechanisms are given, depending on the vertical movement of the working point in the range of ten centimeters. In addition, the dependences of the values of the curvature of the functions of the vertical forces of the three mechanisms on the vertical movement of the working point are obtained by a numerical method. A comparative analysis showed the advantages of the rhombic and three-point mechanisms over the Mezis truss in terms of providing less curvature of the functions of the deflecting force from the displacements of the working point, as well as a smaller number of springs. In rhombic and three-point mechanisms, tension springs are used instead of compression springs in the Mezis truss. The greatest deflecting force with the same spring stiffness and the same overall dimensions of the mechanisms creates a three-point mechanism.